Eliciting the dynamics of leading a sustainable event: Key informant responses - Ensor, J.; Robertson, M.; Ali-Knight, Jane (Cognizant Communication Corporation, 2011)
Within the event management literature relating to network development and festival sustainability there is a paucity of research that analyzes the perception of festival sustainability by festival leaders. After an initial review of the context of sustainability, network theory, and an identification of the changing set of competencies for effective leadership, an exploratory and explanatory investigation is made to elicit and identify the critical factors that key informant festival leaders associate with sustainable festivals. The main purpose of this study is to attain a greater depth of understanding of festival leaders' attitudes towards the dynamics of creating and directing sustainable festivals. Indepth interviews with five elite festival leaders helped to generate the elements of a repertory grid from which a "triading" method was used to elicit constructs. Of the constructs identified, the most significant relate to four areas: the event subject focus; the leadership; the funding; and the organizational culture. The research also revealed that festival leaders conceive sustainability not as an environmental concern, but as a matter of festival survival. Suggestions are then drawn as to the future role of the repertory grid method in identifying and managing stakeholder visions, and future lines of research investigation and application.